2005
DOI: 10.1016/j.envpol.2005.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the rhizosphere-based method with DTPA, EDTA, CaCl2, and NaNO3 extraction methods for prediction of bioavailability of metals in soil to barley

Abstract: The rhizosphere-based method is a preferred approach for evaluating bioavailability of metals in soil. AbstractA rhizosphere-based method was compared with DTPA, EDTA, CaCl 2 , and NaNO 3 extraction methods for the evaluation of bioavailability of heavy metals in soil to barley. The extractable amounts of Cr, Cu, Zn and Cd analyzed by the rhizosphere-based method correlated significantly with the metal content of barley roots. The extractable metals identified by DTPA, EDTA, CaCl 2 and NaNO 3 methods exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
2
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(114 citation statements)
references
References 44 publications
6
96
2
10
Order By: Relevance
“…2), which directly results in the approximate correlation coefficients obtained from both soil fractions ( Table 3) and indicates that both bulk and rhizosphere soils are equally suitable for assessing metal phytoavailability, especially for A-RHIZO and RHIZO methods. This is in contrast with previous results obtained by Feng et al (2005b). This may be due to difference in plant species (wheat versus barley) and growth conditions (greenhouse versus field).…”
Section: Bulk Soils Versus Rhizosphere Soilscontrasting
confidence: 56%
“…2), which directly results in the approximate correlation coefficients obtained from both soil fractions ( Table 3) and indicates that both bulk and rhizosphere soils are equally suitable for assessing metal phytoavailability, especially for A-RHIZO and RHIZO methods. This is in contrast with previous results obtained by Feng et al (2005b). This may be due to difference in plant species (wheat versus barley) and growth conditions (greenhouse versus field).…”
Section: Bulk Soils Versus Rhizosphere Soilscontrasting
confidence: 56%
“…Apesar de o DTPA ter apresentado uma ligeira superioridade entre os métodos de extração avaliados, vários autores não encontraram correlação significativa entre os teores de Pb na planta e os teores no solo extraído com DTPA (ANDRADE et al, 2009;ANJOS;MAGALHÃES e ABREU 2012;FENG et al, 2005). Solo, v. 29, n. 6, p. 977-985, 2005. …”
Section: Resultsunclassified
“…Researchers have found that low-molecular-weight organic acids in the rhizosphere are capable of forming complexes with metal ions in solution and thus enhance the metals' mobilization and uptake by plants (Mench and Martin, 1991;Awad et al, 1994;Krishnamurti et al, 1997;Veeken and Hamelers, 1999;Chen et al, 2003;Gao et al, 2003;Hu et al, 2007;Luo et al, 2008). Feng et al (2005) showed that the extractable amount of Cr, Cu, Zn and Cd by the root exudes correlated significantly with the metal content of barley roots, while the extractable metals identified by DTPA, EDTA, CaCl 2 and NaNO 3 methods exhibited relatively poor or no correlation with the metal content of barley roots. They concluded that the rhizosphere-based method is the most robust approach for evaluation of bioavailability of metals in soil to barley.…”
Section: Introductionmentioning
confidence: 95%